PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN KETERAMPILAN PSIKOMOTOR FISIKA SISWA KELAS X SMA SERI RAMA YLPI PEKANBARU - Susane, Nikki Susane; Nasir, Muhammad Nasir; ', Fakhruddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study is aims at determine learning outcome physic students psychomotor skills application Discovery Learning model at class X Seri Rama YLPI senior high school at Pekanbaru using model Discovery Learning at geometrical optics materials. The research was conducted from March 2015 through June 2015 by 38 research subjects at X1 as experimental group and 27 students at Xz as control group in Seri Rama YLPI senior high school at Pekanbaru. This research is a form of pre-experimental design Intact Group comparasion. The research instrument is physic psychomotor skill achievment test arrange of application aspect adaption. Psychomotor skills learning outcomes studied cover aspects of reading tools, measuring angles with a bow, and planned experiments obtained absorption with good category for its effectiveness in class experiments and categorized effective, whereas for the control class obtained absorption with good enough category and for its effectiveness categorized enough effective. The result of the research indicated of 79,9% absorption of learning at good category in experimental group while 63,2% at good enough category in other group. Thereby concluded that the application Discovery Learning model can improve students physic psychomotor skill in class X Seri Rama YLPI senior hihg school at Pekanbaru. Keywords: Discovery learning model, psychomotor skills, geometrical optics.